PENGEMBANGAN LKS BERBASIS INKUIRI TERBIMBING DENGAN MENGINTEGRASIKAN PENDIDIKAN KARAKTER PADA MATERI IPA KELAS VIII SMP SEMESTER 2 - I Gusti Ayu Agung Widya Adnyani (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2021)
The current science learning outcomes of students are still relatively low due to the limited use of science learning resources, namely Student Worksheets (LKS) which can train students' thinking skills to find their own concepts. Therefore, it is necessary to develop guided inquiry-based worksheets by integrating character education to improve student learning outcomes and form disciplined, honest and curious characters in students. This study aims to develop guided inquiry-based LKS products by integrating character education which is a modification of existing LKS products. Furthermore, the LKS that has been compiled will be tested to determine: (1) the validity of the LKS, (2) the practicality of the LKS, and (3) the effectiveness of the LKS. This type of research is a development research with a Pre-test and Post-test One Group trial design. The instruments used are expert validation assessment guidelines, practicality questionnaires for worksheets and objective questions. Data analysis used quantitative descriptive. The results showed: (1) the average percentage of science expert tests from the content and presentation aspects was 96% very valid criteria and 86% for linguistic and graphic aspects very valid criteria from linguists, (2) met the practical requirements of teachers and students with the average percentage is 87.5%, and (3) meet the effectiveness requirements because the criteria for student learning outcomes include 2 students with very good learning outcomes criteria, 12 students with good learning outcomes criteria, 13 students with fairly good learning outcomes criteria and 5 students with poor learning outcomes criteria.Keywords: LKS, guided inquiry, character education